Measurement and Evaluation of the Online Marketing Training Results for Students at SMA Negeri 1 Bantur, Malang - Bustomi, M. Arief; Rohedi, Ali Yunus; Nurif, Muchammad (Jurnal Sosial Humaniora, 2025)
SMA Negeri 1 Bantur, Malang Regency is located in the southern area of Malang Regency. The demographic conditions and characteristics of theBantur community have caused many Bantur 1 SMA graduates to choose to work rather than continue their education to higher education. As a solution to this condition, the school has provided job training to students for one year as a provision for them after graduation. Apart from being in the form of student knowledge and skills, job training activities also produce goods and services that can be marketed to the public. Therefore, after participating in the training activities, SMA Negeri 1 Bantur students need to also be given training in marketing goods and services. This paper presents the results of training activities for the marketing of goods and services online at SMAN 1 Bantur. The methods used in the training are tutorials and practice using textand video media. Measuring the success of training activities using a questionnaire method and direct assessment of the results of the training participants' practice. The research objective was to obtain a measure of the success of online marketing training activities at SMA Negeri 1 Bantur. Theresults of measuring the success of training and their evaluation can measurethe increase in knowledge and skills of each student who participates in the training.